Analisis Kebijakan terhadap Pengembangan Desa Wisata Golo Loni di Kabupaten Manggarai Timur - Dewi Suryani, Amelia (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Tourism attraction is something that can encourage tourists to visit a tourist destination. Golo Loni Tourism Village is one of the tourism villages in East Manggarai Regency. The purpose of this study was to analyze the policy towards tourism development in Golo Loni village and to formulate strategic steps in the framework of tourism village development. Data were collected through in-depth interviews, document study and observation. Data analysis used descriptive qualitative analysis of tourism potential in Golo Loni Village, village government support in tourism development in Golo Loni and strategic steps in the framework of tourism village development. The results showed that the tourism potential that can be developed in Golo Loni village consists of natural tourism potential, agro-tourism and creative economy potential. Golo Loni tourism village development plan, among others: Attraction development through the creation of tour packages that are packaged in an attractive and structured manner; accessibility development through the provision of adequate infrastructure facilities; amenity development through increasing the carrying capacity of tourist support facilities, and the development of tourism activities both from the community and from the Golo Loni Tourism Village manager to realize sustainable tourism development.